The behaviour of suppliers and consumers in mandated markets: the introduction of the ethanol-petrol blend E10 in Germany - Tosun, Jale (Journal of environmental policy and planning, 2017)
In December 2010, the German government increased the maximum ethanol content that can be blended with petrol from 5% to 10%, which facilitated the introduction of the ethanol-petrol blend E10. The revised ethanol-petrol blend was introduced with ambitions towards decarbonizing the transport sector as well as to support energy security and rural development. While usually supportive of actions aimed to combat climate change, the great majority of German motorists have refused to buy E10. The lacking demand for E10 is the empirical phenomenon addressed by this study. How did the fuel suppliers comply with the policy provisions? Which actors made attempts to influence the motorists’ demand for the new ethanol-petrol blend? Which actor was assigned the responsibility for the problems that occurred upon the rollout of the new fuel type? These research questions guide this study, which concentrates on the behaviour of transport fuel suppliers and consumers in mandated markets, that is, markets created by policy provisions.